Orality and its Metaphors in the Classroom (2020)
This article seeks to contribute theoretically and methodologically to the oral language teaching in the classrooms, specifically in the Colombian high school in what has been called everyday life metaphors. For this purpose, we start with some theoretical considerations about orality as performance and as an oral text; besides, metaphor is defined from the cognitive linguistic. Later, some procedures on everyday life metaphors are exposed, which, for this case, have a strong identity in orality. The paper finishes with the conclusions on the teaching of orality and its metaphors. We highlight that orality -understood as performance or oral text- is another dimension of the knowledge that should not be evaluated from the literate culture